Between grammar and rhetoric : Dionysius of Halicarnassus on language, linguistics and literature - Jonge, Casper Constantijn de, 1977- (Mnemosyne, Supplements, 2008)
The Greek rhetorician Dionysius of Halicarnassus was active in Augustan Rome. For a long time, modern scholars have regarded him as a rather mediocre critic, whose works were only interesting because of the references to earlier scholars and the citations of literary fragments. By interpreting Dionysius' views within the context of his rhetorical programme, this book shows that Dionysius was in fact an intelligent scholar, who combined theories and methods from various language disciplines and used them for his own practical purposes. His rhetorical writings not only inform us about the linguistic knowledge of intellectuals at the end of the first century BC, but also demonstrate the close connections between philology, technical grammar, philosophy, music studies and rhetoric.